Den kulturella betydelsen av ett digitalt pedagogiskt dokumentationsverkyg : en etnografisk studie av Pluttra - Thelin,Henrik (2016)
This study will show what particular elements, by using a digital tool such as Pluttra, in the practice of conducting pedagogical documentation in the Swedish preschools are profound. By conducting an ethnographic fieldwork and participant observation among the preschool teachers at one preschool, and in-depth interviews with two preschool teachers at another preschool, within the same town. The empirical data has been collected and then discussed and analysed, by the aim of a further understanding of the cultural means when using a digital tool in the process of the pedagogical documentation and how it affects the practice of the pedagogical, administrative and analysing work among preschool teachers. The results shows how the digital tool makes the work more effective and flexible due, partly, to the choice of which device being used in the documentation process. Furthermore the digital tool has an important meaning in how it helps, partly by its automatization and centralizing functionality, in the analysing and reflecting work among the teachers at one of the preschools. On the other hand, the teachers at the other preschool found the tool more restricted, as they believe its main purpose is to communicate with the parents. This points out the importance of a standardization of routines and the choice of a standard device, in all of the towns’ preschools. Another important aspect reveals that the perception of presence within a digital context is two folded. First, the presence of the teachers within the physical space when at the same time being within the tool as a teleprescene, and second, the physical space between parent and child are redefined. The specific moments that’s being documented play a crucial part in the tools effectiveness both in relation to involve the children in the documentation process and in the continuing reflections among the teachers, as well as in the dialog between the teachers and children. And finally, the tool itself, could be even more effective and automated than it is today.
Keywords: Fieldwork; ethnography; preschool; children; digital tool; presence; systems; preschool teachers; pedagogical; documentation; automatization; participation; observation; standardization; internet; Pluttra.